Prevalence of Mental Health Stress among Indonesian Islamic Boarding Schools Students in the Early Post-COVID-19: A Cross-Sectional Study - Hengky Irawan; Yuni Asri; Dian Pitaloka Priasmoro; Erik Irham Lutfi (Universitas STRADA Indonesia, 2025)
Background: The COVID-19 pandemic has had a significant impact on students' mental health. However, little is known about its psychological effects on students in Indonesian Islamic boarding schools. Purpose: This study aimed to determine the prevalence of stress among students in Islamic boarding schools and identify the associated contributing factors in the early post-pandemic period. Methods: We conducted a cross-sectional study from March to April 2023 involving 425 students from four Islamic boarding schools in East Java, Indonesia. Participants were selected using a convenience sampling method. Data were collected using a structured questionnaire that included sociodemographic information and the Depression Anxiety Stress Scale-21 (DASS-21) to measure stress levels. Descriptive statistics and multivariate logistic regression analyses were performed to examine the association between stress and various factors. Results: The findings showed that 30.64% of students experienced stress. Factors significantly associated with stress included female gender (OR: 2.17; 95% CI: 1.130–4.190; p < 0.020), length of stay of less than one year (OR: 0.43; 95% CI: 0.204–0.925; p < 0.031), dissatisfaction with allowance (OR, 2.81; 95% CI, 1.238–6.424; p < 0.014), poor communication with friends (OR: 3.60; 95% CI: 1.947–6.659; p < 0.000), and lack of social activities with peers (OR, 4.80; 95% CI, 1.415–16.28; p < 0.012). Conclusion: This study highlights the need for targeted mental health interventions in Islamic boarding schools, particularly those that address financial satisfaction and social relationships. Strengthening peer communication and providing emotional support may help to reduce stress among students in post-pandemic settings.